Development of forced cooling technology using a DLC coating tool with a small through-hole and a communicating tube regarding the turning for difficult-to-machine material - Ikuo TANABE; Hiromi ISOBE (Journal of Machine Engineering)
When a difficult-to-machine material was used for the workpiece, the temperature becomes the melting point over and the tool insert is easily melted. Therefore, in this research, the forced cooling technology using a DLC coating insert with a small through-hole and a communicating tube regarding the turning for difficult-to-machine material was developed and evaluated. The communicating tube was used for supplying the cooling fluid without no-energy, and the cooling fluid using the strong alkaline water with pH 12.5 was used for environmentally friendly. The small through-hole was machined for the cooling function on the insert tip. Then DLC layer with low coefficient of friction for small cutting heat generation was coated on the insert by deposition. The proposed method was finally evaluated using the difficult-to-machine material Ti6Al4V for the workpiece in several experiments; temperature change on the insert tip, tool life, surface roughness on the workpiece after the turning. In addition, the machining time, the running cost and the CO2 emission were also evaluated. It is concluded from the result that (1) The proposed forced cooling technology was very effective for the turning of a difficult-to-machine material, (2) In the proposed method, it is important to maintain the tool tip temperature below 500°C.